Mathematical model of atmospheric carbon dioxide concentration, forest biomass, and coal mining under real data - Moh. Nurul Huda; Agus Suryanto; Isnani Darti; Muhammad Fakhruddin (Modeling Earth Systems and Environment, 2026)

Modeling pneumonia cases with environmental and interregional dependence using a vine copula-based multilayer perceptron - Ahmad Saiful Jamil; Atina Ahdika; Muhammad Fakhruddin; Putu Yuliandari; Sumiati Sumiati (Modeling Earth Systems and Environment, 2026)

Catboost regressor for monsoon rainfall forecasting in Malaysia using atmospheric Beryllium-7 concentration - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Mohd Zaid Hassan Abdul Rahman; Nur Fatini Abdul Ghani; Muhammad Rawi Mohamed Zain (Modeling Earth Systems and Environment, 2026)

A VMD–PSO hybrid framework with machine and deep learning for Aaccurate spatial–temporal daily rainfall occurrence prediction in Pakistan’s diverse climatic regions - Hira Farman; Muhammad Arif Hussain; Sarang Shaikh; Saif Hassan (Modeling Earth Systems and Environment, 2026)

Nonlinear wave dynamics of soliton neuron model: a high-fidelity computational investigation - Usman Younas; Jan Muhammad (Modeling Earth Systems and Environment, 2026)

Ghost-rock karstification and cave system modelling in the Middle Atlas, Morocco - Iliass Naouadir; Salih Muhammad Awadh; Samira Adil; Mohammed Ettaki; El Hassane Chellai; Abdallah Elaaraj; Abdennabi Alitane; Antonio Pulido Bosch; Zaher Mundher Yaseen (Modeling Earth Systems and Environment, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Flash flood susceptibility assessment using an integrated geomorphologic framework in data-scarce arid and semi-arid regions - Aftab Ullah; Rashid Farooq; Abdul Razzaq Ghumman; Muhammad Ejaz Tanveer; Muhammad Atiq Ur Rehman Tariq (Modeling Earth Systems and Environment, 2026)
Flash floods are among the most frequent natural hazards, posing serious environmental challenges, particularly in arid and semi-arid regions where steep topography and compact basin morphometry accelerate surface runoff. The ungauged hill torrents of southwestern Punjab, Pakistan, are particularly vulnerable to such events, experiencing recurrent, intense flash floods. This study develops an integrated GIS-based morphometric framework to assess flash flood susceptibility across 13 major hill torrents in DG Khan and Rajanpur, Punjab. Fifteen morphometric parameters were analyzed using three complementary approaches: Hazard Degree (HD), Principal Component Analysis (PCA), and Analytical Hierarchy Process (AHP). The HD method captured the cumulative influence of all parameters. At the same time, PCA reduced redundancy and identified four dominant controlling factors: length of overland flow (Lo), form factor (Ff), circulatory ratio (Rc), and ruggedness number (Rn). The AHP further incorporated expert judgment, identifying drainage density (Dd) and ruggedness number as the most influential parameters, followed by basin relief (Bh) and drainage frequency (Fs). The convergence of results across the three independent methods significantly improves classification reliability compared to single-method analyses. Three hill torrents (Vidore, Mithawan, and Kaha) were consistently classified as highly susceptible, one as moderately susceptible, and four as low susceptibility. Hence, the proposed integrated HD-PCA-AHP model reduces methodological uncertainty and provides a transferable, data-efficient tool for assessing flash flood susceptibility and managing watersheds in data-scarce arid and semi-arid regions.

A scalable framework for flash flood hazard assessment in data-scarce catchments using coupled modeling - Moiz Ahmed Khan; Muhammad Masood; Mudassar Iqbal; Saliha Qamar; Muhammad Awais Zafar; Khalil Ahmad (Modeling Earth Systems and Environment, 2026)

Mathematical analysis of air pollution dynamics system for emission controls and air filtration technologies with caputo derivative - Muhammad Farman; Khadija Jamil; Saba Jamil; Kottakkaran Sooppy Nisar; Aseel Smerat; Mohamed Hafez (Modeling Earth Systems and Environment, 2026)

Chaotic transitions and multistable regimes in a nonlinear wave model through hybrid analytical–numerical techniques - Muhammad Iqbal; Syeda Sarwat Kazmi; Muhammad Bilal Riaz; Muhammad Aziz Rehman (Modeling Earth Systems and Environment, 2026)
The modified Zakharov–Kuznetsov (mZK) model is a fundamental framework for describing nonlinear phenomena in plasma oscillations, optical systems, discrete electrical lattices, and oceanic wave dynamics. In this work, we establish a unified framework that combines exact solution construction with dynamical systems analysis of the mZK equation. Using the modified Khater method and the Sardar subequation technique under a traveling wave transformation, we derive new and more general families of solitary traveling wave solutions, including trigonometric, hyperbolic, rational, exponential–rational, and complex soliton forms. We show how free parameters govern the existence, shape, and stability of these solutions, with two- and three-dimensional MATLAB simulations illustrating their structures. Furthermore, we reformulate the mZK equation as a planar dynamical system and classify its qualitative features through phase portraits, identifying centers, saddles, and cusps. With the inclusion of periodic external forcing, the reduced system displays bifurcation and chaos, following a period-doubling route with multistability and sensitivity to parameter variations. To the best of our knowledge, this is the first study that simultaneously delivers exact soliton solutions and a complete nonlinear dynamics characterization of the mZK equation. This integrated approach provides a novel template for investigating broader classes of nonlinear evolution equations.

Integrated hydrogeochemical and multivariate statistical assessment of groundwater in Gashua, northeastern Nigeria: implications for arid zone aquifer management - Abdussalam Muhammad Auwal; Martins Uchenna Obidiegwu; Mohammed Yerima Kwaya; Ogechukwu Anastasia Ben-Owope; Josephmartin Izuchukwu Korie; Abdurrasheed Yusuf Muhammad; Musaab A. A. Mohammed; Tamás Madarász (Modeling Earth Systems and Environment, 2026)
Groundwater is the primary source of potable and irrigation water in Gashua, Northeastern Nigeria, where arid climatic conditions limit surface water availability. Unlike previous studies in the Chad Basin that focused on limited chemical parameters, this study applies integrated geospatial modelling and multivariate statistics to delineate hydrochemical facies and anthropogenic hotspots in a semi-arid aquifer. Twenty-five groundwater samples were analyzed for pH, electrical conductivity, total dissolved solids, total hardness, major cations (Ca²⁺, Mg²⁺, Na⁺, K⁺), and anions (Cl⁻, SO₄²⁻, NO₃⁻, HCO₃⁻). Results showed pH values from 5.7 to 7.9, EC between 415 and 1464 µS/cm, and TDS from 265.6 to 937.0 mg/L. 80% (20/25) of the samples exceeded the Nigerian Standard for Drinking Water Quality (NSDWQ) limit for hardness. Piper and Durov diagrams revealed Ca²⁺–Mg²⁺–Cl⁻–SO₄²⁻ and Ca²⁺–Mg²⁺–HCO₃⁻ facies, reflecting carbonate and sulphate dissolution, cation exchange, and evaporative concentration. Spatial analysis delineated recharge zones in the north and discharge zones in the south, with higher salinity and nitrate levels in peri-urban areas. Nitrate ranged from 10.8 to 88 mg/L, with one sample exceeding the World Health Organization (WHO) limit of 50 mg/L; sampling was conducted during the dry season. Principal Component Analysis (PCA) explained 79% of total variance and identified mineralization, pH buffering, and nitrate pollution as key processes. Hierarchical Cluster Analysis (HCA) classified wells into recharge, transitional, and discharge zones. Irrigation suitability assessed by SAR, Na⁺%, PI, KR, and MH confirmed that most samples are suitable, though moderate salinity (C2S1) and isolated sodicity risks highlight the need for site-specific management. These findings emphasize the vulnerability of groundwater to both natural geochemical evolution and human activities. The integrated hydrogeochemical and multivariate approach provides actionable implications: protecting recharge areas in the north, routine surveillance of southern salinity and nitrate hotspots, and tailored farmer advisories for irrigation practices. Such measures are critical for sustainable aquifer management in arid regions.

Hydro-geochemistry and simulation for the sub subsurface environment of groundwater of Shahdara, Pakistan - Muhammad Irfan Jalees; Iqra Younis; Ahmad Ibrahim; Madeeha Batool; Imran Kalim (Modeling Earth Systems and Environment, 2026)

Remote sensing-based 2D hydrodynamic modeling and assessment of the 2014 flood in the Jhelum river basin - Rizwan Mansha; Sajjad Haider; Muhammad Azmat; Hamza Farooq Gabriel; Fahim Ullah (Modeling Earth Systems and Environment, 2026)

Correction: Modeling soil moisture and evapotranspiration dynamics from variably irrigated vegetable fields - Mulatu Liyew Berihun; Girma Worku Awoke; Fitsum Tilahun Teshome; Niguss Solomon Hailegnaw; Tewodros T. Assefa; Muhammad Sohail Waqas; Haimanote K. Bayabil (Modeling Earth Systems and Environment, 2026)

Neural network assisted symbolic analysis and simulation of nonlinear dynamical equation - Jan Muhammad; Fengping Yao; Usman Younas (Modeling Earth Systems and Environment, 2026)

A modelling approach for Mangrove carbon dynamics using integrated optical and SAR data in Balikpapan Bay, Indonesia: algorithm development and accuracy enhancement - A. A. Md. Ananda Putra Suardana; Nanin Anggraini; Muhammad Rizki Nandika; Devica Natalia Br Ginting; Nugraheni Setyaningrum; M. Amar Sajali; Azura Ulfa; Kholifatul Aziz; Kuncoro Teguh Setiawan; Ratih Dewanti Dimyati (Modeling Earth Systems and Environment, 2026)

Spatiotemporal dynamics of a reaction-diffusion nutrient-algae model - Muhammad Waqas Yasin; Mobeen Akhtar; Moutaz Alazab; Mustafa Inc; Zafarullah Baber; Muhammad Sajid Iqbal; Shahram Rezapour (Modeling Earth Systems and Environment, 2026)

Modeling soil moisture and evapotranspiration dynamics from variably irrigated vegetable fields - Mulatu Liyew Berihun; Girma Worku Awoke; Fitsum Tilahun Teshome; Niguss Solomon Hailegnaw; Tewodros T. Assefa; Muhammad Sohail Waqas; Haimanote K. Bayabil (Modeling Earth Systems and Environment, 2026)

Numerical analysis of Williamson nanofluid flow past an oscillating vertical porous plate: influence of Soret, Dufour, and chemical reaction effects - Albara Alrawashdeh; Muhammad Awais; Hakim Al Garalleh; Raja Farrukh Riaz (Modeling Earth Systems and Environment, 2026)

Activation function impact on rainfall prediction: comparative insights across ML and DL architectures - Hira Farman; Muhammad Arif Hussain; Saif Hassan; Sarang Shaikh; Khurshed Ali (Modeling Earth Systems and Environment, 2025)
Rainfall prediction is critical in agriculture, water resource management, transportation, and disaster planning. As a critical component of the hydrological cycle, precisely forecasting daily rainfall helps to lessen the effects of floods, droughts, and other extreme weather events. However, due to the nonlinear and complicated interaction of meteorological factors, daily rainfall forecast remains a grim problem. The proposed work adopts a systematic deep learning-based framework, integrating Long Short-Term Memory (LSTM) and Bidirectional LSTM (BiLSTM) models and Transformers to predict the rainfall of the next day. Besides deep models, a few machine learning classifiers, such as the Logistic Regression (LR), Support Vector Machines (SVM), and the K-Nearest Neighbor (KNN) will be applied to benchmark the performance.One of the main insights in this study is the systematic comparison of a wide variety of activation functions, such as Sigmoid, ReLU, Tanh, Swish, Leaky ReLU, and ELU to measure their effects on model accuracy, convergence, and generalization performance. An experiment was employed on real-life rainfall of the USA dataset, which proved the efficiency of using the BiLSTM model and ReLU and Leaky ReLU activation functions to achieve up to 99% accuracy, whereas Transformer model was also efficient as it obtain up to 98%, but it was not stable and showed a tendency towards occasional instability during the training process. On the contrary, traditional machine learning models displayed an intermediate predictive accuracy, with average accuracies of approximately 87%. Significantly, the results were validated through multi-seed experiments with confidence intervals and baseline benchmarks, demonstrating that the near-perfect scores were not incidental but consistently stable across different initializations. This study provides a new theoretical standpoint in terms of activation functions in deep sequence models as it studies beneficiaries and shortcomings through a mathematical point of view. The results highlight that activation function selection can have an important impact on the accuracy of forecasts and can be significant in building more accurate, scalable, and general learning subroutines in weather predictions.

Investigating higher-dimensional nonlinear evolution equation: dynamics of waves and multistability in fluid mediums - J. Muhammad; U. Younas; Karim K. Ahmed (Modeling Earth Systems and Environment, 2025)

Dynamical transitions and multistability in nonlinear wave systems: dual analytical insights into the geophysical Korteweg–de Vries Equation - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Mohie M. Alqezweeni (Modeling Earth Systems and Environment, 2025)

Analytical solutions of the eighth-order (3+1)-dimensional Kac–Wakimoto equation modeling waves in ocean engineering - Jan Muhammad; Ghulam Hussain Tipu; Usman Younas (Modeling Earth Systems and Environment, 2025)

Stability, soliton dynamics, and bifurcation analysis of the (3+1)-dimensional Sakovich equation in fluid dynamics - Muhammad Arshad; Khurrem Shehzad; Mustafa Bayram; Muhammad Farman; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Bifurcation analysis and turing instability of the ecological model having Beddington–Deangelis-type functional response - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Fengping Yao (Modeling Earth Systems and Environment, 2025)

Dynamics of lumpy skin disease with treatment and viral factor monitoring through fractional operator - Parvaiz Ahmad Naik; Aqeel Ahmad; Qazi Muhammad Farooq; Muhammad Farman; Abdul Ghaffar; Kottakkaran Sooppy Nisar; Aceng Sambas; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

Numerical modelling of vadose zone flow for a shallow groundwater wetland using HYDRUS-1D - Muhammad Usman; Lloyd H. C. Chua; Kim N. Irvine; Lihoun Teang (Modeling Earth Systems and Environment, 2025)
This study employs HYDRUS-1D for modelling the vadose zone processes in a shallow groundwater wetland. HYDRUS-1D is based on Richards equation whose numerical solution heavily relies on reliable data derived from soil water retention curves. This modelling was supported by extensive field and laboratory measurements. Both disturbed and undisturbed soil samples were collected at the four depths for determination of particle size distribution, bulk density, saturated hydraulic conductivity, and saturated water content. The van Genuchten retention curves were used to describe the relationship between pressure head and water content; model parameters were optimized through inverse modelling with initial estimates of residual water content, shape parameters (α and n) obtained from ROSETTA model 3 (provided in HYDRUS-1D) and saturated water content and saturated hydraulic conductivity, determined from laboratory tests. Independent measurements of soil moisture and soil tension measured both in the field and laboratory fit well with the water retention curve obtained from the optimized ROSETTA parameters. Model performance in simulating measured water contents was good (average RMSE = 0.02 m 3 /m 3 ) during calibration and validation (0.01 m 3 /m 3 and 0.03 m 3 /m 3 for two independent periods). Water content in upper soil layers was strongly influenced by atmospheric conditions, while groundwater level has the most influence in the bottom layers. Evapotranspiration was found out to be the dominant process in summer with total flux higher than that of infiltration while in winter evapotranspiration was relatively lower, even though still higher than infiltration.

Dual approach artificial neural networks-fractional order operator to enhancing in vitro fertilization predictions and success measure - David Amilo; Khadijeh Sadri; Evren Hincal; Muhammad Farman; Kottakkaran Sooppy Nisar (Modeling Earth Systems and Environment, 2025)

Correction to: Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Wave propagation and multistability analysis to the modified fractional KDV-KP equation in diversity of fields - Jan Muhammad; Usman Younas (Modeling Earth Systems and Environment, 2025)

Stability and chaos control of a fractional-order model for CO$$_2$$ emissions in the environment - Muhammad Farman (Modeling Earth Systems and Environment, 2025)

Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Exploring soliton and chaotic dynamics in the generalized reaction duffing equation using multiple analytical methods - Azad Ali Sagher; Muhammad Imran Asjad; Md. Mamunur Roshid; Suhad Ali Osman Abdallah (Modeling Earth Systems and Environment, 2025)

Exploring the fixed point theory and numerical modeling of fish harvesting system with Allee effect - Muhammad Waqas Yasin; Mobeen Akhtar; Nauman Ahmed; Ali Akgül; Qasem Al-Mdallal (Modeling Earth Systems and Environment, 2025)

Spatio-temporal patterns and Turing–Hopf bifurcation in a spatially extended prey–predator model with ratio-dependent interactions - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Dumitru Baleanu; Ovidiu Tintareanu-Mircea (Modeling Earth Systems and Environment, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

Exploring land cover change impacts on ecosystem services using machine learning technique and scenario simulation: case study of the Upper Citarum River Basin, Indonesia - Andi Muhammad Yasser Hakim; Budi Heru Santosa; Dwi Nowo Martono; Dionysius Bryan Sencaki; Hari Prayogi; Robby Arifandri; Apip Apip; Widya Ningrum; Kai Schröter; Max Jacob Steinhausen (Modeling Earth Systems and Environment, 2025)

Investigation of lassa fever with relapse and saturated incidence rate: mathematical modeling and control - Aqeel Ahmad; Usama Atta; Muhammad Farman; Kottakkaran Sooppy Nisar; Hijaz Ahmad; Evren Hincal (Modeling Earth Systems and Environment, 2025)

Dynamics of bi-susceptibility patterns in Covid-19 outbreaks and associated abstain strategies - Waheed Ahmad; Muhammad Rafiq; Azhar Iqbal Kashif Butt; Momina Zainab; Naeed Ahmad (Modeling Earth Systems and Environment, 2025)

Development of a hydrodynamic model of the irrigation canal network by using HEC-RAS: a case study of Layyah Canal Division, Pakistan - Numan Ijaz; Sajjad Haider; Muhammad Muaaz (Modeling Earth Systems and Environment, 2025)

Modeling source identification of dust and paint metals effecting workshops indoor air quality: associated contamination and cancer risk - Kashif Hussain; Muhammad Hassan Bashir; Hamaad Raza Ahmad; Muhammad Tahir Shehzad; Amna Zulfqar (Modeling Earth Systems and Environment, 2025)

Mathematical study of infectious disease of pines caused by bark beetles - Takasar Hussain; Muhammad Ozair; Adnan Aslam; Maham Afaq; Muhammad Tanveer; Muhammad Awais; J. F. Gómez-Aguilar (Modeling Earth Systems and Environment, 2025)

Chaos and forecasting financial risk dynamics with different stochastic economic factors by using fractional operator - Muhammad Farman; Kottakkaran Sooppy Nisar; Mumtaz Ali; Hijaz Ahmad; Muhammad Farhan Tabassum; Abdul Sattar Ghaffari (Modeling Earth Systems and Environment, 2025)

Investigating co-dimension one and two bifurcations in a discrete-time epidemic model with vaccination and vital dynamics - Muhammad Aqib Abbasia; Maria Samreena; Ekrem Savasb; J. F. Gómez-Aguilarc (Modeling Earth Systems and Environment, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

Investigating the dynamics of (3+1)-dimensional generalized nonlinear physical system via sensitivity and phase portraits - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman (Modeling Earth Systems and Environment, 2025)

Exploring chaos and stability: dynamic insights into the stochastic Davey-Stewartson system through advanced sensitivity analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Tomas Kozubek; Muhammad Aziz-ur-Rehman (Modeling Earth Systems and Environment, 2025)
In this study, we investigate the stochastic Davey-Stewartson equation in the presence of noise. These two-dimensional integrable equations are higher-dimensional versions of the nonlinear Schrödinger equation. Davey-Stewartson equations are important in plasma physics, nonlinear optics, hydrodynamics, and other disciplines because the solutions they provide are valuable in understanding many complex physical phenomena. We employ a modified version of the $$\left( \frac{G'}{G^2} \right)$$ G ′ G 2 approach to handle variable-coefficient systems with imaginary components, such as nonlinear Schrödinger systems. We have discovered a wide range of precise traveling wave solutions, including solitons, kink, periodic, and rational solutions. These solutions may have a significant impact in the domains of engineering and plasma physics. The presented techniques effectively achieve a variety of exponential solutions, including bright, dark, single, rational, and periodic solitary wave solutions. We used MATLAB to simulate our findings and provide 3D, 2D, and counter graphs that illustrate the impact of noise on the precise solutions of the stochastic Davey-Stewartson problem. We apply the Galilean transformation to derive the planar dynamical system, which enhances our understanding of the system’s dynamical analysis. We also conduct a sensitivity analysis to observe the systematic response to various initial conditions. This analysis focuses on the symmetrical aspects of the system and includes the illustration of phase portraits with equilibrium points. We also investigate the chaotic behavior of the planer dynamical system by introducing an additional external force. We predict the system’s behavior to increase the value of intensity and frequency. Our analysis reveals periodic, quasi-periodic, and chaotic processes.

A novel numerical approach for the assessment of the seepage failure, predictive modelling of seepage through non-homogenous earth-fill dams resting on pervious foundations using artificial neural networks - Muhammad Zeeshan Khursheed; Badee Alshameri; Waqas Hassan; Lokmane Abdeldjouad (Modeling Earth Systems and Environment, 2025)

Spatial modelling of regional drought severity index based on multiple criteria analysis using cloud-based remote sensing data in agriculture land - Khalifah Insan Nur Rahmi; Muhammad Dimyati; Mangapul Parlindungan Tambunan; Jalu Tejo Nugroho (Modeling Earth Systems and Environment, 2025)

Unraveling the complexity of solitary waves in the Klein-Fock-Gordon equation: dynamical insights into bifurcation and Chaos analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Dilawaiz (Modeling Earth Systems and Environment, 2025)

Mathematical analysis of chickenpox population dynamics unveiling the impact of booster in enhancing recovery of infected individuals - Kabiru Garba Ibrahim; James Andrawus; Abbas Abubakar; Abdullahi Yusuf; Stephen Ishaya Maiwa; Kefas Bitrus; Muhammad Sani; Ibrahim Abdullahi; Sunday Babuba; Joseph Jonathan (Modeling Earth Systems and Environment, 2025)

Modeling and analysis of a carbon capturing system in forest plantations engineering with Mittag–Leffler positive invariant and global Mittag–Leffler properties - Muhammad Umer Saleem; Muhammad Farman; Rabia Sarwar; Parvaiz Ahmad Naik; Perwasha Abbass; Evren Hincal; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

Flood monitoring and reservoir management in the transboundary Chenab River Basin using machine learning and remote sensing techniques - Amatul Baseer; Muhammad Farooq Iqbal (Modeling Earth Systems and Environment, 2025)

Lyapunov global stability analysis and effects of serial killing on community disorder with generalized Mittag–Leffler kernel properties - Kottakkaran Sooppy Nisar; Aqeel Ahmad; Muhammad Farman; Evren Hincal; Rabia Sarwar (Modeling Earth Systems and Environment, 2025)

Evaluating Digital Elevation Model generation from Sentinel-1 SAR data in challenging tropical environments - Zylshal Zylshal; Athar A. Bayanuddin; Sartika Sartika; J. Indri Pratiwi; Andie Setyoko; Rahmat Arief; Muhammad Rokhis Khomarudin (Modeling Earth Systems and Environment, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Modeling the dynamics of dengue fever with double susceptibility and optimal control strategies - Muhammad Younas Khan; Saif Ullah; Muhammad Farooq; Muhammad Bilal Riaz (Modeling Earth Systems and Environment, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Mathematical modeling of Ebola using delay differential equations - Ali Raza; Nauman Ahmed; Muhammad Rafiq; Ali Akgül; Alicia Cordero; Juan R. Torregrosa (Modeling Earth Systems and Environment, 2024)
Nonlinear delay differential equations (NDDEs) are essential in mathematical epidemiology, computational mathematics, sciences, etc. In this research paper, we have presented a delayed mathematical model of the Ebola virus to analyze its transmission dynamics in the human population. The delayed Ebola model is based on the four human compartments susceptible, exposed, infected, and recovered (SEIR). A time-delayed technique is used to slow down the dynamics of the host population. Two significant stages are analyzed in the said model: Ebola-free equilibrium (EFE) and Ebola-existing equilibrium (EEE). Also, the reproduction number of a model with the sensitivity of parameters is studied. Furthermore, the local asymptotical stability (LAS) and global asymptotical stability (GAS) around the two stages are studied rigorously using the Jacobian matrix Routh–Hurwitz criterion strategies for stability and Lyapunov function stability. The delay effect has been observed in the model in inverse relation of susceptible and infected humans (it means the increase of delay tactics that the susceptibility of humans increases and the infectivity of humans decreases eventually approaches zero which means that Ebola has been controlled into the population). For the numerical results, the Euler method is designed for the system of delay differential equations (DDEs) to verify the results with an analytical model analysis.

Exploring vortex dynamic efficiency in hydro-suction system: a combined experimental and numerical investigation - Mohammed Hamid Rasool; Mohd Remy Rozainy Mohd Arif Zainol; Norizham Abdul Razak; Muhammad Khairi A. Wahab; Neeraj Bhardwaj (Modeling Earth Systems and Environment, 2024)

Predicting the rock cutting performance indices using gene expression modeling - Turab H. Jafri; Muhammad Naqeeb Nawaz; Jun-Sik Park; Syed Taseer Abbas Jaffar; Rahat Hussain; Tae-Min Oh (Modeling Earth Systems and Environment, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Gene expression programming-based multivariate model for earth infrastructure: predicting ultimate bearing capacity of rock socketed shafts in layered soil-rock strata - Muhammad Naqeeb Nawaz; Muhammad Haseeb; Sana Ullah Qamar; Waqas Hassan; Arfan Shahzad (Modeling Earth Systems and Environment, 2024)

Advanced AI approach for enhanced predictive modeling in reservoir characterization within complex geological environments - Wakeel Hussain; Muhammad Ali; Rakhshanda Sadaf; Harith F. Al-Khafaji; Izhar Sadiq; Chuanyu Hu; Hamza Daud; Salah Alshareef Alkfakey Ahmed (Modeling Earth Systems and Environment, 2024)

Pore-scale simulation of flow in porous rocks for wall shear stress analysis - Yusron Feriadi; Muhammad Rizqie Arbie; Umar Fauzi; Fariduzzaman (Modeling Earth Systems and Environment, 2024)

Enhanced climate projections over Sindh, Pakistan: a bayesian model averaging ensemble methodology - Aatka Irfan; Firdos Khan; Muhammad Abbas; Shaukat Ali (Modeling Earth Systems and Environment, 2024)

Modeling spatial distribution of earthquake epicenters using inhomogeneous Log-Gaussian Cox point process - Salma Anwar; Muhammad Yaseen; Muhammad Yaseen; Yasir Latif (Modeling Earth Systems and Environment, 2024)

Comparison of Seepage Evaluation Methods for Earth-Filled Embankments: A Case Study of Sukian Dyke, Mangla Dam - Muhammad Hamza Khalid; Tanzeela Yasmin; Badee Alshameri; Syed Muhammad Jamil; Waqas Hassan (Modeling Earth Systems and Environment, 2024)

An election algorithm combined with support vector regression for estimating hydrological drought - Mohammed Achite; Somayeh Emami; Muhammad Jehanzaib; Okan Mert Katipoğlu; Hojjat Emami (Modeling Earth Systems and Environment, 2024)

Calibration interval scenario approach in spatial modeling of land cover change in East Kalimantan from 2016 to 2036 - I Wayan Gede Krisna Arimjaya; Ade Komara Mulyana; Muhammad Dimyati (Modeling Earth Systems and Environment, 2024)
Spatial modeling can be used to predict future land cover changes based on past and present conditions. However, it is not yet known to what extent this model can be used to predict the future with reliable accuracy. Therefore, by using multi-temporal land cover data, this study aims to build an optimal model based on the calibration interval scenario. The optimal model is then used to predict and analyze changes in land cover in East Kalimantan in 2016–2036. 11 classified multi-temporal land cover maps from the Landsat Time Series using Random Forest in Google Earth Engine are used to model 14 calibration interval scenarios. A land Change Modeler is used to model and predict land cover change with 14 driving variables. The results of the classification of multi-temporal land cover maps show a good level of accuracy, with an Overall Accuracy value of 71.43–85.14% and a Kappa value of 0.667–0.827. Then 2016–2021 is one of the best scenarios with 5-year intervals where the accuracy of future predictions can still be relied upon for up to three prediction iterations. The calibration interval scenario approach in spatial modeling in East Kalimantan can be relied upon to show a decrease in forest cover from 2016 to 2021, with a deforestation rate of 651 km 2 /year. The prediction of land cover in 2036 estimates that the remaining forest cover area in East Kalimantan is 69.203 km 2 . It is believed that topography is the most influential variable driving land cover change in East Kalimantan.

A comparison of experimental and computational methods for circular footing response on lime-treated geotextile reinforced silty sand - Syed Md Yousuf; Mehboob Anwar Khan; Syed Muhammad Ibrahim; Anil Kumar Sharma; Furquan Ahmad; Pramod Kumar (Modeling Earth Systems and Environment, 2024)

Marshall-Olkin length biased exponential distribution for wind speed analysis alternative to Weibull distribution - Muhammad Ahsan ul Haq; Sharqa Hashmi; Muhammad Aslam (Modeling Earth Systems and Environment, 2024)

Predicting long term regional drought pattern in Northeast India using advanced statistical technique and wavelet-machine learning approach - Shahfahad; Swapan Talukdar; Bonosri Ghose; Abu Reza Md. Towfiqul Islam; Md. Hasanuzzaman; Ishita Afreen Ahmed; Bushra Praveen; Asif; Aruna Paarcha; Atiqur Rahman; A. S. Gagnon; Muhammad Afzal (Modeling Earth Systems and Environment, 2024)

Prediction and mapping of land degradation in the Batanghari watershed, Sumatra, Indonesia: utilizing multi-source geospatial data and machine learning modeling techniques - Fajar Yulianto; Puguh Dwi Raharjo; Irfan Budi Pramono; Muhammad Anggri Setiawan; Galdita Aruba Chulafak; Gatot Nugroho; Anjar Dimara Sakti; Sapto Nugroho; Syarif Budhiman (Modeling Earth Systems and Environment, 2023)

Patterns of coral diseases linked to the impact of climate change: a case study of scleractinia corals in Southeast Sulawesi, Indonesia’s coral triangle - La Ode Muhammad Yasir Haya; Ratna Diyah Palupi; Subhan Subhan; Rahmadani Rahmadani (Modeling Earth Systems and Environment, 2023)

Correction: Comparative studies of enhancing oil recovery optimization for optimum oil feld development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Azizullah Shaikh; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Modeling milkfish farming in the land around the nickel-processing plant in North Konawe District, Southeast Sulawesi, Indonesia - Muhammad Aswar Limi; Hesty Sukma Dewi (Modeling Earth Systems and Environment, 2023)

Optimizing the dynamics of bone turnover with genetic algorithm - Muhammad Idrees; Ayesha Sohail (Modeling Earth Systems and Environment, 2023)

Hydrogeophysical modeling and physio-chemical analysis of quaternary aquifer in central part of Bari Doab, Punjab, Pakistan - Shahbaz Muhammad; Muhammad Irfan Ehsan; Perveiz Khalid; Asma Sheikh (Modeling Earth Systems and Environment, 2023)

Comparative studies of enhancing oil recovery optimization for optimum oil field development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Higher order Gibbs point process modeling of 2005-Kashmir earthquakes - Salma Anwar; Muhammad Yaseen; Syed Amer Mahmood (Modeling Earth Systems and Environment, 2023)

Assessing long-term coral reef degradation in Indonesia’s Tiworo strait marine conservation area using remote sensing and rapid appraisal for fisheries approaches - La Ode Muhammad Yasir Haya; Baru Sadarun; Muslim Tadjudah; Analuddin Kangkuso; La Ode Alirman Afu; Asrin Ginong Pratikino; Amadhan Takwir; Masahiko Fujii (Modeling Earth Systems and Environment, 2022)

Modelling impacts of climate change on coastal West African rainfall - Christopher E. Ndehedehe; Muhammad Usman; Onuwa Okwuashi; Vagner G. Ferreira (Modeling Earth Systems and Environment, 2022)

Modeling implications of climate induced streamflow changes on the fish species of the Soan River, Pakistan - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas (Modeling Earth Systems and Environment, 2022)

Change in forest biomass with altitudinal variations in dry temperate forest of Dir Kohistan, Pakistan - Syed Tufail Ahmad; Ahmad Hussain; Saif Ullah; Aitezaz Muhammad Khan; Muhammad Sadiq Khan; Inam Ullah (Modeling Earth Systems and Environment, 2022)

Modeling streamflow using multiple precipitation products in a topographically complex catchment - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas; Oluwafemi E. Adeyeri (Modeling Earth Systems and Environment, 2022)

Strauss point modeling for seismic activity: a case study of earthquakes - Amna Zahra; Ijaz Hussain; Muhammad Zaffar Hashmi; Muhammad Faisal; Elsayed Elsherbini Elashkar; Sadaf Shamshoddin Soudagar; Fares Fawzi Al-Deek; Mohammed Ageli (Modeling Earth Systems and Environment, 2022)

A sustainable generalization of inverse Lindley distribution for wind speed analysis in certain regions of Pakistan - Muhammad Shoaib; Irum Sajjad Dar; Muhammad Ahsan-ul-Haq; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2022)

Evaluating the suitability of two parametric wind speed distributions: a case study from Pakistan - Muhammad Ahsan ul Haq; Sohail Chand; Muhammad Zahir Sajjad; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2021)

Investigating the impact of injection-water salinity and well strategies on water mobility and oil production in an oil-wet reservoir - Muhammad Jawad Khan; Temoor Muther; Hassan Aziz; Muhammad Mubeen-ur-Rehman (Modeling Earth Systems and Environment, 2021)

Streamflow forecasting by modeling the rainfall–streamflow relationship using artificial neural networks - Shahzad Ali; Muhammad Shahbaz (Modeling Earth Systems and Environment, 2020)

Groundwater quality assessment for drinking purpose: a case study from Sindh Industrial Trading Estate, Karachi, Pakistan - Muhammad Jahangir Khan; Bilal Ahmed Shah; Bassam Nasir (Modeling Earth Systems and Environment, 2020)

An experimental and modelling approach to produce biochar from banana peels through pyrolysis as potential renewable energy resources - Anurita Selvarajoo; Dinie Muhammad; Senthil Kumar Arumugasamy (Modeling Earth Systems and Environment, 2020)

Modeling predictive assessment of wind energy potential as a power generation sources at some selected locations in Pakistan - Muhammad Abid Khan; Hüseyin Çamur; Youssef Kassem (Modeling Earth Systems and Environment, 2019)

Sedimentary units-layering system and depositional model of the carbonate Mishrif reservoir in Rumaila oilfield, Southern Iraq - Heba Sadoon Al-Mimar; Salih Muhammad Awadh; Abdullah A. Al-Yaseri; Zaher Mundher Yaseen (Modeling Earth Systems and Environment, 2018)

Development of streamflow prediction models for a weir using ANN and step-wise regression - Muhammad Hassan; Haseeb Zaffar; Imran Mehmood; Anwar Khitab (Modeling Earth Systems and Environment, 2018)

Evaluating the variability and trends in extreme climate events in the Kashmir Valley using PRECIS RCM simulations - Ishfaq Gujree; Ishfaq Wani; Muhammad Muslim; Majid Farooq; Gowhar Meraj (Modeling Earth Systems and Environment, 2017)

Statistical methodology for biosorption of nitrate (NO3 −) ions from aqueous solution by Pleurotus eryngii fungal biomass - Farah Amin; Farah Naz Talpur; Aamna Balouch; Hassan Imran Afridi; Muhammad Ali Surhio (Modeling Earth Systems and Environment, 2017)

Vulnerability assessment of an agro-stressed aquifer using a source-pathway-receptor model in GIS - Yawar Hussain; Sadia F. Ullah; Abdul Q. Aslam; Muhammad B. Hussain; Gulraiz Akhter; Hernan E. Martinez-Carvajal; Frédéric Satgé; Arshad Ashraf; Bilal Iqbal; Martin Cárdenas-Soto (Modeling Earth Systems and Environment, 2017)